SLIP EFFECTE ON MAGNETO HYDRO DYNAMICS CASSON FLUID FLOW IN THE INFLUENCE OF THERMAL AND SORET RADIATION (International Journal of Food and Nutritional Sciences, 2022)
This paper presents in detail the numerical results for the two-dimensional steady and mixed convection motion of numerous slip contributions on MHD Casson liquid with Soret coupled to thermal radiation. Equations for the flow model are D.E.with greater than one independent variable (PDEs), often known as equations for species momentum and energy. Through the use of similarity variables, these model equations are modelled to ODE’s. Runge-Kutta Fehlberg is used in conjunction with the shooting method to solve the simplified nonlinear ODEs. Key parameters that affect concentration, skin friction, temperature, velocity, heat rate, and mass movement are described subjectively and visually.